Horizontal cooperation in logistic: Opportunities and impediments for logistic service providers in the Central key economic region, Vietnam - Trần Lê Diệu Linh; Lê Mỹ Kim (My University, 2020)
Horizontal cooperation in logistic: Opportunities and impediments for logistic service providers in the Central key economic region, Vietnam
Keywords: Horizontal cooperation; Logistics; Central Vietnam